Análisis de la inaplicación de la suspensión de los efectos del acto administrativo, por parte los tribunales distritales de lo contencioso administrativo. - Jiménez Soto, Eli Obaldo (2024)
The thesis present below has the scientific purpose of discovering and proposing an alternative solution to the research problem. Entitled Analysis of the Non-Application of the Suspension of the Effects of the Administrative Act by the District Courts of Administrative Litigation One of the main characteristics and privileges of the Public Administration of a State is administrative self-protection, which serves as the mechanism for administrative control and justice; a peculiarity that enables it to implement its decisions and execute its acts from the moment they are issued, unless a regulation states otherwise. The execution of the acts is carried out even with the opposition of the directly affected Administrated, through means of forced execution. The justification or reason for this lies in the principle of efficiency as an essential element of the Administration's actions in its obligation to serve the general interests. It should be noted that the execution of acts is independent of whether they are being challenged in the administrative or judicial avenues, adhering to the principle of legality. Precisely, a marked difference highlighted by the General Organic Code of Processes regarding the Administrative Contentious Procedure is the introduction of the legal institution of the suspension of the contested act in Article 330, which aims to cease the legal effects produced by the contested administrative act while it is being processed. This innovation responded to the large number of administrative acts that were declared illegal, in a proportion of 55:100, that is, out of every 100 acts challenged in court, 55 were declared illegal, making it imperative that Article 330 of the COGEP be applied by the judges.